Evaluation of High-Throughput PCR and Microarray-Based Assay in Conjunction with Automated DNA Extraction Instruments for Diagnosis of Sepsis - Laakso, Sanna; Kirveskari, Juha; Tissari, Päivi; Mäki, Minna (PLOS ONE, 2011)
Background High incidence of septic patients increases the pressure of faster and more reliable bacterial identification methods to adapt patient management towards focused and effective treatment options. The aim of this study was to assess two automated DNA extraction solutions with the PCR and microarray-based assay to enable rapid and reliable detection and speciation of causative agents in the diagnosis of sepsis. Methodology/Principal Findings We evaluated two automated DNA instruments NucliSENS® easyMAG® and NorDiag Arrow for the preparation of blood culture samples. A set of 91 samples flagged as positive during incubation was analyzed prospectively with the high-throughput generation of Prove-it™ Sepsis assay designed to identify over 60 Gram-negative and Gram-positive bacterial species as well as methicillin resistance marker from a blood culture. Bacterial findings were accurately reported from 77 blood culture samples, whereas 14 samples were reported as negative, containing bacteria not belonging to the pathogen panel of the assay. No difference was observed between the performance of NorDiag Arrow or NucliSENS® easyMAG® with regard to the result reporting of Prove-it™ Sepsis. In addition, we also assessed the quality and quantity of DNA extracted from the clinical Escherichia coli isolate with DNA extraction instruments. We observed only minor differences between the two instruments. Conclusions Use of automated and standardized sample preparation methods together with rapid, multiplex pathogen detection offers a strategy to speed up reliably the diagnostics of septic patients. Both tested DNA extraction devices were shown to be feasible for blood culture samples and the Prove-it™ Sepsis assay, providing an accurate identification of pathogen within 4,5 hours when the detected pathogen was in the repertoire of the test.